A Mental Health Training Format for Adult Education Teachers. (June 2017) - Meek, Fiona; Specht, Jacqueline; Rodger, Susan
The present study investigated the needs of adult education staff pertaining to adult students' mental health issues within a local school board. The study utilized mixed-methods design and was divided into progression of three separate studies. An initial focus group was conducted to identify the 12 participants' concerns and provide a direction for the needs assessment survey that was administered to the entire population of adult education teachers in the board. Two 2-hr workshops were designed for the 114 members of the staff based on the needs identified by the surveys. An evaluation of the workshops indicated that the workshops were valuable and further training was desired. By educating teachers about students who are learning in the context of mental health challenges, we will be able to provide them with the necessary tools to do their jobs more successfully and comfortably.